2018
DOI: 10.1111/jog.13638
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological map of Toxoplasma gondii infection and associated risk factors in preconception period in China: A nationwide cross‐sectional study

Abstract: There were significant regional variations in Toxoplasma gondii seropositivity and associated risk factors among Chinese women of reproductive age during preconception period. This calls for a targeted primary prevention strategy. Screening and treatment before conception and preconception health education may have potential for reducing congenital Toxoplasmosis in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Surprisingly, migrant women showed a lower risk of past TOX infection as compared with native women, which could be explained by several mechanisms connected to the healthy migrant effect (HME). Previous studies observed signi cant regional variations in the prevalence of human TOX infection with the trends increasing from West China to East China, which coincided with the incidence of TOX infection in food animals [24,25]. As an economically developed province, Guangdong has attracted a huge number of migrant populations from the less developed central and western regions.…”
Section: Migrant Status and Torch Infectionsmentioning
confidence: 96%
“…Surprisingly, migrant women showed a lower risk of past TOX infection as compared with native women, which could be explained by several mechanisms connected to the healthy migrant effect (HME). Previous studies observed signi cant regional variations in the prevalence of human TOX infection with the trends increasing from West China to East China, which coincided with the incidence of TOX infection in food animals [24,25]. As an economically developed province, Guangdong has attracted a huge number of migrant populations from the less developed central and western regions.…”
Section: Migrant Status and Torch Infectionsmentioning
confidence: 96%
“…Toxoplasmosis in China is a consistent problem, despite being lower 43 than the commonly accepted world average 1,44 ; according to nationwide studies involving several thousands of examined humans, the national prevalence of toxoplasmosis fluctuated from 5.9% in the early ‘90 s 45 to 7.9% in the ‘00 s 46 . A more recent nationwide study involving 2,008,561 women before pregnancy reported even lower prevalence (2.6%) 47 , depicting a decreasing trend in younger generations in rural areas. Similar trend has been identified in the nationwide survey as well 46 , where the highest prevalence regards citizens over 80 years old.…”
Section: Introductionmentioning
confidence: 91%
“…Although there is no evidence of increased risk of Toxoplasma infection for plumbers who are frequently exposed to sewage water [87], oocysts are persistent and prevalent in water, soil, and foods [88]. Also, vegetarians and certain occupations such as farmers are significantly more associated with Toxoplasma IgM seropositivity [89].…”
Section: Interpretation Of Toxoplasma Serologymentioning
confidence: 99%